Strategies, tips & activities for the effective band director targeting student engagement and comprehension - Linaberry, Robin (Routledge, 2021)
STRATEGIES, TIPS & ACTIVITIES FOR THE EFFECTIVE BAND DIRECTOR: TARGETING STUDENT ENGAGEMENT AND COMPREHENSION is a resourceful collection of highly effective teaching strategies, solutions, activities, games and alternative options for band directors. Chapters are aligned to common topics, and present several practical lesson ideas for each topic. In most cases, each pedagogical suggestion is supported by a specific passage excerpted from standard concert band literature. Topics covered include: Percussion Section management; Group and Individual Intonation; Instructional Techniques for Rhythm-Meter-Tempo-Pulse; Phrasing & Interpretation; Increasing Lesson Attendance; Score Study Shortcuts; Curriculum development; Seating Auditions; Organizational Strategies; Phrasing and Interpretation and much more. This collection of very specific concepts, ideas and reproducible pedagogical strategies - not unlike mini Lesson Plans - can be used easily and immediately. As a band director of students at all levels, from elementary to adult, they were devised during more than three decades of practice with some borrowed, revised and adapted from scores of successful teachers & clinicians"--